# Solving Simultaneous Equations Using Substitution(KS4, Year 10)

homesitemapsimultaneous equationssolving simultaneous equations using substitution
Simultaneous equations are a set of several equations with several unknowns. We can use the substitution method to find the values of the unknowns which solve both equations at the same time. An unknown from one equation is substituted into the other equation, allowing one unknown to be found in one equation.

## How to Solve Simultaneous Equations Using the Substitution Method

Solving simultaneous equations using the substitution method is easy.

## Question

Solve the simultaneous equations shown below using the substitution method.
We can substitute Equation (1) into Equation (2).

## 1

Equation (1) tells us that y = 2x. Substitute this value of y into Equation (2).
x + 2x = 3

## 2

Solve for x.
 x + 2x = 3 3x = 3 Add the like x terms 3x ÷ 3 = 3 ÷ 3 Divide both sides by 3 x = 1
x = 1 is a solution to the simultaneous equations.

## 3

Substitute the variable we have just found (x = 1) into one of the equations. Solve for y.
 y = 2x Substitute into Equation (1) y = 2( 1 ) y = 2 × 1 y = 2
y = 2 is a solution to the simultaneous equations.

We have solved the simultaneous equations:

x = 1, y = 2 solves

y = 2x

x + y = 3

## A Real Example of How to Solve Simultaneous Equations Using the Substitution Method

The example above was simple. Equation (1) told us what "y = ". In the following example, we will have to find what "y = " by rearranging one of the equations. Note: you could find what "x = "... it doesn't matter which unknown you substitute.

## Question

Solve the simultaneous equations shown below using the substitution method.

## 1

Rearrange Equation (2) to find "y =".
 x − y = 1 x − y + y = 1 + y Add y to both sides x = 1 + y x − 1 = 1 + y − 1 Subtract 1 from both sides x − 1 = y y = x − 1
We have rearranged x − y = 1 to find what "y = ". y = x − 1

## 2

Rearranged Equation (2) tells us that y = x − 1. Substitute this value of y into Equation (1).

x + ( x − 1 ) = 5

## 3

Solve for x.
 x + x − 1 = 5 2x − 1 = 5 Add the like x terms 2x − 1 + 1 = 5 + 1 Add 1 to both sides 2x = 6 2x ÷ 2 = 6 ÷ 2 Divide both sides by 2 x = 3
x = 3 is a solution to the simultaneous equations.

## 4

Substitute the variable we have just found (x = 3) into one of the equations. Solve for y.
 x + y = 5 Substitute into Equation (1) 3 + y = 5 3 + y − 3 = 5 − 3 Subtract 3 from both sides y = 2
y = 2 is a solution to the simultaneous equations.

We have solved the simultaneous equations:

x = 3, y = 2 solves

x + y = 5

x − y = 1

## Lesson Slides

The slider below shows another real example of how to solve simultaneous equations using the substitution method.

This page was written by Stephen Clarke.

## You might also like...

#### Help Us Improve Mathematics Monster

• Do you disagree with something on this page?
• Did you spot a typo?
Please tell us using this form.

#### Find Us Quicker!

• When using a search engine (e.g., Google, Bing), you will find Mathematics Monster quicker if you add #mm to your search term.